2012
DOI: 10.1039/c2cp42520c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DEMS study of ethanol oxidation: effect of surface structure and Sn surface modification

Abstract: Using the dual thin layer flow through cell, a semi-quantitative analysis of the volatile products during the electrooxidation of adsorbed and bulk solution of 0.01 M ethanol at polycrystalline platinum, smooth, roughened and Sn modified Pt(11,1,1), Pt(311) electrodes has been done by on-line differential electrochemical mass spectroscopy (DEMS). In addition to the current efficiency of CO(2), that of acetaldehyde was determined as a function of the flow rate. At polycrystalline platinum, ethanol oxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Mostafa et al [22] observed a CO 2 product yield of 1% in comparison to CH 3 CHO (55%) and CH 3 COOH (44%) during EOR on Pt/C. Ethane 1,1 diol [11] was also detected as a product of EOR which forms as result of hydrolysis of CH 3 CHO.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mostafa et al [22] observed a CO 2 product yield of 1% in comparison to CH 3 CHO (55%) and CH 3 COOH (44%) during EOR on Pt/C. Ethane 1,1 diol [11] was also detected as a product of EOR which forms as result of hydrolysis of CH 3 CHO.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…(1) (2) A DEMS study for the ethanol oxidation reaction (EOR) on Pt has shown that EOR mainly forms CO 2 , CH 3 CHO and CH 3 COOH [18,22,39,40]. Mostafa et al [22] observed a CO 2 product yield of 1% in comparison to CH 3 CHO (55%) and CH 3 COOH (44%) during EOR on Pt/C.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease at E<0.6 V is a consequence of the COads re-poisoning of the surface and the diminution of oxidation rates as the electrode potential diminishes [38,39]. However, this process depends on the surface structure and on the pH of the electrolyte.…”
Section: Ethanol Oxidation At Low Phsmentioning
confidence: 99%
“…In this experiment, an ethanol solution is flown through the cell at 0.4 V for two minutes, to allow the cleavage of ethanol molecules and adsorption of fragments. After that, the solution is changed to a solution containing only the supporting electrolyte at the same pH and then the electrode is cycled between 0.04 and 0.95 V vs RHE at v=5 mVs -1 , registering simultaneously the Faradic and mass spectrometric ion currents [39,43]. to CH4 at low potentials [36,44] whereas I44 in this particular case only gives information about CO2 formed, since ethanol has been removed from the solution.…”
Section: Ethanol Stripping Experimentsmentioning
confidence: 99%